On the Solution of n-Product of 2D-Hadamard–Volterra Integral Equations in Banach Algebra - Mohamed M. A. Metwali; Manochehr Kazemi; Shami A. M. Alsallami (Journal of Mathematics)
In this study, the solvability of a general form of product type of n-classes of 2D-Hadamard–Volterra integral equations in the Banach algebra C1,a×1,b is studied and investigated under more general and weaker assumptions. We use a general form of the Petryshyn’s fixed point theorem (F.P.T.) in combination with a suitable measure of noncompactness. This forms a generalization of the Schauder, Darbo, and classical Petryshyn’s F.P.T. The problem under study encompasses various integral equations, as different special cases have been previously investigated in the literature. Finally, we present several illustrative examples to validate our underlying assumptions.